On the Design of Global Refunding and Climate Change - Hans Gersbach; Ralph Winkler (ETH Zurich, CER-ETH - Center of Economic Research, 2007)
We design a global refunding scheme as a new international approach to address climate change. A global refunding system allows each country to set its carbon emission tax, while aggregate tax revenues are partially refunded to member countries in proportion to the relative emission reductions they achieve within a given period, compared to some given baseline emissions. In a simple model we show that a suitably designed global refunding scheme is self-enforcing and achieves the social global optimum
Keywords: H23; Q54; H41; 330; climate change mitigation; global refunding scheme; international agreements; self-enforcing mechanisms; Klimawandel; Umweltpolitik; Ökosteuer; Trittbrettfahrerverhalten; Steuervergünstigung; Theorie